Three new species of Polyalthia (Annonaceae) from Thailand and Laos - Bunchalee, Pasakorn; Johnson, David M.; Murray, Nancy A.; Chalermglin, Piya (Phytotaxa, 2021)
Three new species of Polyalthia are described and illustrated. Two of the new species are part of the Polyalthia evecta species complex, while the third species belongs to a species group including P. cinnamomea and P. stenopetala.